Comparing the Modified History, Electrocardiogram, Age, Risk Factors, and Troponin Score and Coronary Artery Disease Consortium Model for Predicting Obstructive Coronary Artery Disease and Cardiovascular Events in Patients With Acute Chest Pain. Issue 3 (September 2019) - Teressa, Getu; Bhasin, Varun; Noack, Pamela; Poon, Michael
Abstract : The objective of this study was to compare the History, Electrocardiogram, Age, Risk factors, and Troponin (HEART) score and clinical coronary artery disease (CAD) consortium (CADC) model for predicting obstructive CAD (≥50% stenosis on coronary computed tomographic angiography) and 30-day major adverse cardiovascular events (MACE, composite of acute myocardial infarction, revascularization, and mortality). We studied 1981 patients with no known CAD who presented with acute chest pain and had negative initial troponin and electrocardiogram. Chest pain was classified as typical, atypical, and nonanginal and used to score the history component of the modified HEART score. The C-statistic for predicting obstructive CAD was 0.747 [95% confidence interval (CI), 0.712–0.783] for the HEART score and 0.792 (95% CI, 0.762–0.823) for the CADC model ( P = 0.0005). The C-statistic for predicting 30-day MACE was 0.820 (95% CI, 0.774–0.864) for the HEART score and 0.850 (95% CI, 0.800–0.891) for the CADC model ( P = 0.11). Among the 48.3% of patients for whom the CADC model predicted ⩽5% probability of obstructive CAD, the observed 30-day MACE was 0.6%; among the 48.9% of patients for whom the HEART score was ⩽2, the 30-day MACE was 0.6%. In conclusion, the CADC model was more effective at predicting obstructive CAD compared to the HEART score. The HEART score and CADC model were equally effective to safely identify low-risk patients by achieving <1% missed 30-day MACE.